2000
DOI: 10.1111/j.1447-0756.2000.tb01305.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Transforming Growth Factor‐β1 with Myometrial Invasion of Endometrial Carcinomas through Effects on Matrix Metalloproteinase

Abstract: Myometrial invasion of endometrial cancers involves an increase in gelatinase activity, regulated to some extent by TGF-beta 1 in an autocrine or paracrine fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…TGF-␤1 and TGF-␤2, which were unable to trigger MMP-9 expression by these cells, did not stimulate the invasiveness of KLE cells. Others had reported that TGF-␤1 increased invasiveness in KLE cells (20), but in the latter study TGF-␤1 increased MMP-9 expression by KLE cells, which nonetheless supports our findings that increased MMP-9 expression confers invasive properties to endometrial carcinoma cells. The fact that TGF-␤3 induces the expression of MMP-9 by KLE cells suggests the presence of a positive loop for regulation of autocrine TGF-␤3 tumor promoting effect, because MMP-9 can activate latent TGF-␤ isoforms into their active forms (26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TGF-␤1 and TGF-␤2, which were unable to trigger MMP-9 expression by these cells, did not stimulate the invasiveness of KLE cells. Others had reported that TGF-␤1 increased invasiveness in KLE cells (20), but in the latter study TGF-␤1 increased MMP-9 expression by KLE cells, which nonetheless supports our findings that increased MMP-9 expression confers invasive properties to endometrial carcinoma cells. The fact that TGF-␤3 induces the expression of MMP-9 by KLE cells suggests the presence of a positive loop for regulation of autocrine TGF-␤3 tumor promoting effect, because MMP-9 can activate latent TGF-␤ isoforms into their active forms (26).…”
Section: Discussionsupporting
confidence: 92%
“…lines. High levels of TGF-␤1 transcripts are presents in KLE cells, in agreement with previous reports of TGF-␤1 production by endometrial carcinoma cells in vitro and in vivo (19,20). In addition, the KLE cell line is tumorigenic when injected subcutaneously in nude mice and invasive (21), which indicates a late stage phenotype and legitimates the evaluation of the invasion promoting effects of TGF-␤s.…”
Section: Discussionsupporting
confidence: 90%
“…To fill this data gap, we explored the antitumor effect of progesterone on TGFb signaling at three levels: ligands, receptors, and SMADs. High levels of TGFbs are present in endometrial carcinoma cells in vitro and in vivo (38)(39). TGFb isoforms have been shown to act on endometrial cell growth by autocrine or paracrine mechanisms and are implicated in several processes of tumorigenesis and metastasis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have shown that TGF-ß induces the expression of MMPs (like MMP-2, MMP-9, MMP-10) in several human cancer cell lines, such as prostate (31), bladder (13), breast (32), endometrial (33), oral (29) and ovarian cancer (12). However, no previous study has investigated a possible correlation between serum levels of MMP-2 and TGF-ß in melanoma.…”
Section: Discussionmentioning
confidence: 99%